Factors influencing the selection towards islamic microfinance / Fatin Nursyafira Ghazali - Ghazali, Fatin Nursyafira (Faculty of Business and Management, 2015)
Islamic microfinance and Halal certified microentrepreneurs are Shari’ah compliant business sector sharing similar values, market and principles. In contrast, there has been disconnection between the Islamic microfinance and micro entrepreneurs in Malaysia. Despite from the growth of Islamic banking in Malaysia, the development of micro-enterprise has seemed to be a backbone for most of the country in the world including Malaysia. Even though more than a half of total population in Malaysia is Malays in which the religion majority in Islam, there is still low penetration of Islamic microfinance among the micro entrepreneurs in Malaysia. Therefore, this paper aims to explore the factors that affecting the selection towards Islamic microfinance among the micro entrepreneurs.